Predicting outcome of repair of medial meniscus posterior root tear with early osteoarthritis using bone single-photon emission computed tomography/computed tomography - Whi, Wonseok (Medicine (Baltimore), 2020)
Repair of medial meniscus posterior root tear (MMPRT) is considered as an effective early intervention strategy for osteoarthritis. We aimed at evaluating whether or not single-photon emission computed tomography/computed tomography (SPECT/CT) could predict the treatment outcome. Eleven patients with MMPRT who underwent preoperative SPECT/CT were retrospectively enrolled. Clinical symptoms were evaluated based on the knee injury and osteoarthritis outcome score (KOOS) and visual analogue scale (VAS) for pain. The uptake pattern of the medial tibial plateau (MTP) on SPECT/CT was visually assessed. Additionally, the maximum lesion-to-cortical counts ratio (LCR(max)) for the anterior and posterior aspects of MTP and anterior-posterior MTP ratio (APR) were quantitatively assessed. Spearman correlation analyses were performed between the change in clinical symptom scores and preoperative SPECT/CT patterns. All patients showed increased radiotracer uptake in MTP. Among them, 8 (73%) showed dominant uptake in the anterior aspect of MTP. The rest 3 (27%) showed posterior-dominant uptake. Patients with anterior-dominant patterns tended to show better outcomes in terms of the postoperative KOOS score (P = .07). Anterior MTP LCR(max) showed a negative correlation with the change in VAS (ρ = −0.664, P < .03). APR showed a correlation with the change in the KOOS score (ρ = 0.655, P < .03). Patients with MMPRT with relatively higher uptake in the anterior aspect of MTP could have better clinical outcomes after the repair. The preoperative SPECT/CT pattern may have a predictive value in selecting patients with good postoperative outcomes.